VD_FINDINFO Décision / 2022 / 81 vom 27. November 2021 - VD Tribunal cantonal (2021)
FRAIS DE LA PROCÉDURE, INDEMNITÉEN GÉNÉRAL, DROIT D'ÊTRE ENTENDU | 29 al. 2 Cst., 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH)